KINERJA PEGAWAI DALAM PELAYANAN KESEHATAN DI PUSKESMAS SIDUK KABUPATEN KAYONG UTARA - Saprianti E.42009027 (FISIP Universitas Tanjungpura Pontianak, 2013)
This essay aims to identify and anlyze the employee’s performance in health service in Siduk Community Health Center. The little is health based on issue occur in health service that is lacking of maximum servise caused by employee’s performance which is not optimal.This study uses a descriptive type of research with a qualitative approac. The subject of reseach are employees of Siduk Community Health Center who involed in health service and community who do health service. Resulth of this research in the employee’s performance in excuting health service in Siduk Community Health Center isn’t optimal yet. Indicators that user are effectiveness and efficiency, authority and responsibility, discipline and initiative. Which have to be upgraded to intensity employee’s performance to create the optimal service.Based on the purpose and result of research, the sugestions are intensity Employee’s performance, more responsible employee toward the aunthory, intensity discipline, and communication between employee’s. Keywords : Employee’s, performance, service, health.